2018
DOI: 10.1007/s11356-018-2447-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of phthalate exposure with anthropometric indices and blood pressure in first-grade children

Abstract: We aimed to assess the relationship of urine phthalate metabolite concentrations with anthropometric indices, and blood pressure in first-grade children. We detected 11 phthalate metabolites in urine and estimated anthropometric indices, including skinfold measurements, waist circumference (WC), and body mass index (BMI) in 276 children aged 6-8 years. Multivariate linear regression models were used to assess the associations between urinary phthalate metabolite levels, and anthropometric and blood pressure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…Our findings align with previous cross-sectional research, which demonstrated a similar association between MCOP and diastolic blood pressure among US children and adolescents (35,36). Similarly, we found that MEHHP was associated with increased diastolic blood pressure; these findings align with those among a cohort of Chinese children (37). These findings collectively may suggest that associations between toxicants and blood pressure begin earlier in life and are consistent through adulthood.…”
Section: Sensitivity Analysissupporting
confidence: 91%
“…Our findings align with previous cross-sectional research, which demonstrated a similar association between MCOP and diastolic blood pressure among US children and adolescents (35,36). Similarly, we found that MEHHP was associated with increased diastolic blood pressure; these findings align with those among a cohort of Chinese children (37). These findings collectively may suggest that associations between toxicants and blood pressure begin earlier in life and are consistent through adulthood.…”
Section: Sensitivity Analysissupporting
confidence: 91%
“…However, one study described positive associations between MEP, MBP, and MBP, and obesity indices in girls, with negative associations in boys (93). Exposure levels of school-aged to adolescents to non-DEHP metabolites (MMP, MEP, MBP, MiBP, and MBzP) were mostly positively associated with one or more anthropometric indices in school-aged children or adolescents (89,91,92,94,96,102,(105)(106)(107)(108)(109)(110). In contrast, after sex stratification, inconsistent associations were evident (94,102,107,110).…”
Section: Environmental Phthalates and Obesitymentioning
confidence: 99%
“…The metabolites were analyzed in the School of Laboratory Medicine, Hubei University of Chinese Medicine by liquid chromatography-mass spectrometry (LC-MS/MS; Agilent, USA), according to the method for urine phthalates measurement described in Specht et al (Specht et al, 2015). This method was also validated in our previous study (Wu et al, 2018b). The stored urine sample were thawed, and approximatedly 200 μL of each sample was vortexd, sonicated for 5 min, and buffered using ammonium acetate.…”
Section: Intervention Strategymentioning
confidence: 99%